1984
DOI: 10.1016/0022-3115(84)90703-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of compression properties and swelling of beryllium irradiated at various temperatures

Abstract: A beryllium cylinder irradiated * 2 (E > 1 MeV) was cut into samples and tested. Yield strength and plastic strain was determined in compression tests at 300, 723, 823 K and after annealing at 1173 K for one hour. The Immersion density and helium content were measured on samples. An equation for swelling was derived from the data by regression analysis. The microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…For a comparison with more recent results, the total amount of gas from each isotope produced in the beryllium reflector was calculated after 21 cycles of irradiation and it was found that the amounts of 3 T, 3 He, and 4 He are, respectively, 9.57, 0.00621, and 94.0 g. These results, especially for the…”
Section: Comparison To Previous Gas Production Studiesmentioning
confidence: 89%
See 4 more Smart Citations
“…For a comparison with more recent results, the total amount of gas from each isotope produced in the beryllium reflector was calculated after 21 cycles of irradiation and it was found that the amounts of 3 T, 3 He, and 4 He are, respectively, 9.57, 0.00621, and 94.0 g. These results, especially for the…”
Section: Comparison To Previous Gas Production Studiesmentioning
confidence: 89%
“…However, monitoring 3 He, as well as 6 Li, is important because these isotopes are strong thermal neutron absorbers and could potentially lead to degradation of the beryllium properties as a neutron reflector.…”
Section: Althoughmentioning
confidence: 99%
See 3 more Smart Citations